The resurrectionist ebook - Dunlap, A. Rae (2024)
In the tradition of The Alienist and Anatomy: A Love Story, a decadently macabre, dark and twisty gothic debut set in 19th century Scotland – when real-life serial killers Burke and Hare terrorized the streets of Edinburgh – as a young medical student is lured into the illicit underworld of body snatching. Historical fiction, true crime, and dark academia intertwine in a harrowing tale of murder, greed, and the grisly origins of modern medicine for readers of Lydia Kang, ML Rio, Sarah Perry, and C.E. McGill. "With wit as sharp as a scalpel, and a plot as dark and twisted as the Edinburgh alleys in which it is set, The Resurrectionist is a thrilling debut that will have readers turning pages deep into the night." —Hester Fox, author of The Last Heir to Blackwood Library Library Reads Selection for December 2024 | Aardvark Book Club Pick for December 2024 | Paste Magazine Most Anticipated Historical Fiction Books of Fall 2024 | Buzz Book Selection for Spring/Summer 2025 | BookBub Best New Horror for January 2025 | The Strand January Mystery Pick of the Month | Criminal Element Most Anticipated Reads: December 2024 | The Escapist Best New Horror Books Coming in December 2024 | A/V Club Books You Should Read in December 2024 | BookRiot Most-Anticipated New Queer Books Out in December 2024 Edinburgh, Scotland, 1828. Naïve but determined James Willoughby has abandoned his posh, sheltered life at Oxford to pursue a lifelong dream of studying surgery in Edinburgh. A shining beacon of medical discovery in the age of New Enlightenment, the city's university offers everything James desires—except the chance to work on a human cadaver. For that, he needs to join one of the private schools in Surgeon's Square, at a cost he cannot afford. In desperation, he strikes a deal with Aneurin "Nye" MacKinnon, a dashing young dissectionist with an artist's eye for anatomy and a reckless passion for knowledge. Nye promises to help him gain the surgical experience he craves—but it doesn't take long for James to realize he's made a devil's bargain . . . Nye is a body snatcher. And James has unwittingly become his accomplice. Intoxicated by Nye and his noble mission, James rapidly descends into the underground ranks of the Resurrectionists—the body snatchers infamous for stealing fresh corpses from churchyards to be used as anatomical specimens. Before he knows it, James is caught up in a life-or-death scheme as rival gangs of snatchers compete in a morbid race for power and prestige. James and Nye soon find themselves in the crosshairs of a shady pair of unscrupulous opportunists known as Burke and Hare, who are dead set on cornering the market, no matter the cost. These unsavory characters will do anything to beat the competition for bodies. Even if it's cold-blooded murder . . . Exquisitely macabre and delightfully entertaining, The Resurrectionist combines fact and fiction in a rollicking tale of the risks and rewards of scientific pursuit, the passions of its boldest pioneers, and the anatomy of human desire.